2008
DOI: 10.1152/ajpcell.00365.2008
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the temporal effects of vasoconstrictors on PKC translocation and Ca2+ signaling in single resistance arterial smooth muscle cells

Abstract: Arterial smooth muscle (ASM) contraction plays a critical role in regulating blood distribution and blood pressure. Vasoconstrictors activate cell surface receptors to initiate signaling cascades involving increased intracellular Ca(2+) concentration ([Ca(2+)](i)) and recruitment of protein kinase C (PKC), leading to ASM contraction, though the PKC isoenzymes involved vary between different vasoconstrictors and their actions. Here, we have used confocal microscopy of enhanced green fluorescence protein (eGFP)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…Recent studies have shown a clear translocation of PKC␣ from the cytosol to the membrane following stimulation with a phorbol ester in aortic and arterial smooth muscle cells (43,49). More specifically for our studies, the Ca 2ϩ -dependent isoforms PKC␣, ␤I, and ␤II show a strong endogenous presence in HEK293 cells (44).…”
Section: Kir62 Subunit Regulation By Pkcsupporting
confidence: 56%
“…Recent studies have shown a clear translocation of PKC␣ from the cytosol to the membrane following stimulation with a phorbol ester in aortic and arterial smooth muscle cells (43,49). More specifically for our studies, the Ca 2ϩ -dependent isoforms PKC␣, ␤I, and ␤II show a strong endogenous presence in HEK293 cells (44).…”
Section: Kir62 Subunit Regulation By Pkcsupporting
confidence: 56%
“…Because PKC activity is generally reflected by changes in membrane-association of the enzyme (31,35,45), the effect of ET-1 on levels of membrane-localized PKC␣, ␤I, or ␤II were assessed in intrapulmonary arteries from sham and E-IH rats by Western blotting (3,43). Intrapulmonary arteries were isolated as above and placed in Arterial PO2, PCO2, and pH following 4 wk eucapnic intermittent hypoxia (E-IH) exposure.…”
Section: Effects Of E-ih On Pkc Membrane Localizationmentioning
confidence: 99%
“…We have shown previously that UTP causes mobilization of PKCα, δ and ε in these cells (9). However, examination of the PKC dependence revealed that both contraction and the increased Ca 2+ in response to UTP were relatively insensitive to Tat-linked membrane permeable peptide inhibitors of PKC (see Fig.…”
Section: Discussionmentioning
confidence: 70%
“…We have shown that the vasoconstrictors AngII, ET-1 and UTP all mobilize PKCα, PKCδ and PKCε in mesenteric smooth muscle cells (9). We investigated the extent of various PKC isoform involvement in UTP induced contractions by using Tat-linked membrane permeable peptide inhibitors targeting particular PKC isoforms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation